Bezpośrednie inwestycje zagraniczne na Litwie w okresie transformacji systemowej - Ładysz, Jerzy; Czetwertyński, Sławomir (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Foreign direct investment (FDI) is an important element of globalization and integration of European Union countries. The example of Lithuania - one of the new member states - approves global tendencies in changes of geographical and brand structure of FDI, and also shows the role of FDI as a key factor of economic development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 179-190